Watch me sleep: Self-surveillance and aging queer performance anxiety - McLeod, Dayna (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2023)
Watch me sleep is a video essay that compares Restless, a video installation comprised of night-vision surveillance footage of Dayna McLeod and her girlfriend sleeping, with an excerpt of Under Surveillance: 12hrs at the PHI, a live-feed performance that featured her sleeping alone at the PHI Centre—an arts research and exhibition centre in Montreal—that was livestreamed as part of a fifteen-day broadcasting program in February 2021. This video essay puts in conversation different affective moments of sleeping between these projects: one for an installation where the artist had editing control over footage of her sleeping self and what was eventually shown to an audience, and the other, where she had little to no control over what was shown to the original livestreaming audience because she was asleep.